Analisis Pemeriksaan Kehamilan K6 Di Wilayah Kerja Puskesmas Kotakaler Kabupaten Sumedang - Ely Walimah; Nabilah Nur Azizah (Awatara Publisher, 2026)
All pregnant women have the right to receive high-quality comprehensive prenatal care, especially Antenatal Care (ANC) examinations at least six times (K6) in accordance with the Indonesian Minister of Health Regulation Number 21 of 2021, as crucial in reducing maternal mortality (AKI) and infant mortality (AKB). The achievement of K6 at the Kotakaler Health Center in 2024 shows a figure of 98.87% with an estimate of 101.16%. The purpose of this study is to find out what factors affect the achievement of K6 coverage in the work area of the Kotakaler Health Center, Sumedang Regency. The method is qualitative with a case study approach through in-depth interview techniques to related parties. The results of the study identified high population mobility in urban areas as the main factor that hinders the achievement of K6 coverage, this factor makes it difficult to continuously monitor ANC visits. In addition, the existence of abortion cases also reduces the number of targets that can reach K6. Comprehensive strategies such as indoor and outdoor activities have been implemented. Good knowledge of pregnant women and a positive attitude towards pregnancy examinations support compliance to conduct complete pregnancy examinations, the accessibility of health services has also been supported, complete infrastructure, and the availability of adequate health human resources. However, external challenges such as population mobility still require an adaptive approach.